Authoritarian Parenting and Self-Concept With Emotional Maturity on Students at SMA - Amri, Raudatul; Dewi, Ismira (Empathy : Jurnal Fakultas Psikologi, 2023)
Pola asuh otoriter dan konsep diri dengan kematangan emosi siswa SMA Adolescence is considered an emotionally difficult time. This is because teenagers who ignore many stimuli can cause emotional outbursts. Adolescents with mature emotions give a stable emotional reaction, not changing from one feeling or mood to another. Emotional maturity in adolescents is necessary to get parental attention, especially what happens in adolescents. This study examines the relationship between authoritarian parenting and self-cothe ncept of passionate matmaterial students SMA Negeri 4 Tanjungpinang. The method used in this study is quantitative. The variables in the study were measured using the emotional maturity scale, authoritarian parenting scale, and self-concept. The population in the study were students of class XI at SMA Negeri 4 Tanjungpinang. The sample of this study was 82 students at SMA Negeri 4 Tanjungpinang obtained through a simple random sampling technique. The data analysis used in this study is multiple regression analysis with the help of SPSS version 22.0 for Windows. The result of data analysis showed: (1) there is a very significant relationship between authoritarian parenting and selself-concept with emotional maturity in students, (2) there is a very substantial negative relationship between authoritative parenting and emotional maturity in students, (3) there is a very substantial positive relationship between self-concept and emotional maturity on students. This study concludes that there is a relationship between authoritarian parenting and self-concept and emotional maturity in students.